Increasing the effectiveness of crowdfunding campaigns - Kalaš, Robert; Lukeš, Martin, 1976-; Svobodová, Ivana, 1969-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2016)
The aim of this thesis is to analyze crowdfunding campaigns on Kickstarter, and contribute towards increasing the effectiveness of such campaigns, as most campaigns are unsuccessful. The theoretical part will focus on defining crowdfunding as the new phenomena of capital distribution and compared with other forms of financing new ideas. The empirical part focuses on a paired comparison analysis of campaigns from two various locations and three industries in total. Factores affecting the successfulness are analyzed and a pattern which would help towards solving the initial problem is looked for. The aim of the thesis was fulfilled by giving recommendations which have an impact on the success rate.
Vedoucí práce: Martin Lukeš
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses